BRONCANO RODRÍGUEZ, F. (2020). Conocimiento expropiado. Epistemología política en una democracia radical. Madrid: Akal. - Medina Vizuete, Lola (Daimon Revista Internacional de Filosofia, 2024)
Reseña de BRONCANO RODRÍGUEZ, F. (2020). Conocimiento expropiado. Epistemología política en una democracia radical. Madrid: Akal.